Analisis Seni Mural Café Wow Madiun Dari Point Of View Komunikasi Visual Karya Studio Imaginer House - Sean Elbert Jeremiah; Haryanto Haryanto; Wida Wida (FKIP Universitas Palangka Raya, 2022)
Art is developing in today's era, one of its manifestations is mural art. Imaginary House Studio is a mural-making studio. The Imaginer House mural has visual communication, one of which is the mural at the WOW Madiun café. Café WOW Madiun is located at Cokroaminoto street No. 116, Cheese, Taman’s districts, Madiun City, East Java. The approach of this research uses a qualitative approach. Meanwhile, the type of research that will be used is descriptive research. The analysis of the mural art of WOW Madiun café from the point of view of visual communication by the Imaginary House studio. From the results of the research, there are three main parts, namely themes, principles of visual communication, and meaning. The theme in the WOW Madiun café mural is socio-cultural and environmental. The principle of visual communication is using cartoon-style illustrations. In the mural cafe WOW Madiun, warm colors and cool colors are applied. The unity found in the WOW Madiun café mural has the principle of proximity. greater proportion of the object image. Finally, the WOW Madiun café mural has an asymmetrical balance design principle. The WOW Madiun cafe mural has 2 meanings, namely denotative and connotative. In other words, mural art itself is not just a painting on a large area or wall, but has a visual communication point of view, both in terms of themes, design principles, and the meanings contained in the mural.